Football Intelligence Training and Tactics for Soccer Success - Teoldo, Israel; Guilherme, Jose; Garganta, Julio (Routledge, 2022)
"Soccer is the biggest game in the world and has proved to be an unprecedented phenomenon of social impact, inhabiting a prominent place in the daily lives of millions of human beings, a game that has impact even in the most remote of places. In an ever-changing world, of soccer coaching and tactics, player intelligence has become increasingly important, providing the essential ability to act effectively in a given moment. Therefore, in recent years, the tactical component has been increasingly valued and diffused. Around the world, this dimension of sport performance is being studied and applied by many professionals in the field, from the youth academies all the way through to the professional level. This book is designed to help those who devote much of their time to improving the quality of the game, by coaching and training highly informed, creative and intelligent players. These coaches devote their time and energy to improve players and teams' performances. In turn, match analysts, physiotherapists, psychologists, clinicians, and the sport science team dedicate themselves to optimize resources that help boosting the performance levels of the players, the coaches and the team. Football Intelligence: Training and Tactics for Soccer Success presents procedures and ideas that, besides assisting in the task of evaluating the tactical performance of soccer players and teams, also allows improving their expression throughout the learning and training phase. This book will be key reading for football coaches and players alike, as well as students and practitioners of sport psychology and performance analysis"--